EVALUATING BIOSTATISTICAL COMPETENCIES FOR MEDICAL STUDENT:: THE BENEFITS OF A BIOSTATISTICS CENTRE DEVELOPMENT (Proceedings of the International Conference on Public Health, 2017)
Biostatistics represents a critical methodological skill for medical and health researchers, as statistical methods are increasingly a important part of medical and health research. The need for medical and health researchers to understand the process of statistical investigations and be able to plan statistical inquiry in medical and health related decisions justifies the ongoing integration of biostatistical training into medical institution educational settings. In this respect, Faculty of Medicine University of Muhammadiyah Malang (FMUMM) initiate to develop Biostatistics Center for Medical and Health Research (BCMHR) called MEARS (Medical and Health Research Statistics) for medical student. Thus there exists a need to investigate the difference of biostatistical competencies between medical students who collaborated with MEARS in their research and the others who not collaborated with. A cross sectional study was conducted on 221 medical student in FMUMM.  The study subjects were distributed questionnaire which related to the knowledge regarding the practice of biostatistics among the study subjects. The result of medical students who collaborated with MEARS were significantly higher than those who not collaborated with (p = 0,0000). This indicating the benefits of a biostatistics centre development in medical faculty that can help medical student to develop a conceptual understanding of statistical ideas and their applications.
Keywords: biostatistics, Evidence-Based Medicine, research, methodological skill